Triple Mutation Epidermal Growth Factor Receptor (EGFR) Exon 18 (G719S), 20 (T790M) and 21 (L858R) in a Male Patient with Lung Adenocarcinoma: A Case Report - Nur Marleta Riza; Daniel Maranatha (Faculty of Medicine Universitas Airlangga, 2020)
Background: Lung cancer is one of the deadliest cancers in the world. The percentage of non small cell lung cancer (NSCLC) is about 80% of the incidence of lung cancer. The type of NSCLC, adenocarcinoma, is usually found in the presence of epidermal growth factor receptor (EGFR) mutations.Case. A male patient aged 70 years, an active smoker, works as a farmer. He has complained of shortness of breath, and chest pain for three months. There was no family history of suffering from malignancy. The cytology result of the right pleural fluid indicated adenocarcinoma. He was diagnosed with pulmonary adenocarcinoma (D) stage IV positive mutation of EGFR exon 18 (G719S), 20 (T790M) and 21 (L858R) carnofsky score 70. He could survive for more than 11 months with the treatment of EGFR TKI, and received a good therapeutic response. Initially, for the first six months it was such a progressive disease, and for the next eleven months it became stable.Conclusion: In addition to the exon mutations found in this case, the cells in the tumor will continue to grow and develop into new mutants that are immune such drugs and rapidly split themselves into new, different forms. The therapy for complex mutations is still being developed. EGFR TKI therapy in this patient had a relatively good response. Further understanding of the molecular biology of lung cancer is seriously required.